A way with worms - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Pesticide use on the Caribbeans favourite veggie, the spinach-like callaloo (Amaranthus sp.), can be reduced by between 45 and 85% using two integrated approaches launched by the Caribbean Agricultural Research and Development Institute (CARDI)....